DETERMINAN PERTUMBUHAN KREDIT MODAL KERJA PERBANKAN DI INDONESIA: Pendekatan Error Correction Model (ECM) - Sasanti Widyawati; Setyo Tri Wahyudi (Jurnal Keuangan dan Perbankan, 2016)
AbstractBank loans has an important role in financing the national economy and driving force of economic growth.Therefore, credit growth must be balanced. However, the condition show that commercial bank credit growthslowed back.Using the method of Error Correction Model (ECM) Domowitz - El Badawi, the study analyze theimpact of short-term and long-term independent variables to determine the credit growth in Indonesia financialsector. The results show that, in the short term only non performing loans are significant negative effect onthe working capital loans growth. For long-term, working capital loan interest rates have a significant negativeeffect, third party funds growth have a significant positive effect and inflation have a significant negativeeffect.